2018
DOI: 10.12669/pjms.344.15018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intraocular pressure, Corneal thickness, and Retinal nerve fiber layer thickness in patients with Obstructive Sleep Apnea Syndrome

Abstract: Objective:To evaluate the intraocular pressure (IOP), central corneal thickness (CCT), and peripapillary retinal nerve fiber layer (RNFL) thickness in Patients with Obstructive Sleep Apnea Syndrome.Methods:In this prospective study, 103 patients with OSAS (study group) and 37 healthy subjects were enrolled. All participants underwent comprehensive ophthalmic examinations. Mean outcome measures were intraocular pressure by Goldmann applanation tonometry, CCT measurement using ultrasound pachymeter and peripapil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
8
3
Order By: Relevance
“…Nadarajah et al [23] did not determine any significant alteration in the IOP values in patients with OSAS compared with the control cases, but they defined decreased corneal hysteresis in OSAS, which may be another link between this disease and the development of glaucoma. Teberik et al [24] reported that there were no significant differences between the OSAS patients and control cases regarding the IOP, central corneal thickness, or RNFL values in all quadrants.…”
Section: Discussionmentioning
confidence: 97%
“…Nadarajah et al [23] did not determine any significant alteration in the IOP values in patients with OSAS compared with the control cases, but they defined decreased corneal hysteresis in OSAS, which may be another link between this disease and the development of glaucoma. Teberik et al [24] reported that there were no significant differences between the OSAS patients and control cases regarding the IOP, central corneal thickness, or RNFL values in all quadrants.…”
Section: Discussionmentioning
confidence: 97%
“…Kaya et al 30 reported a significant difference between the OSAS groups and the control group, whereas no significant difference was identified between AHI and corneal thickness. Teberik et al 31 reported a decreased corneal thickness in patients with OSAS than in the control group, although not to a statistically significant degree, and no significant relationship was identified with the degree of AHI. That said, the fact that patients in the control groups were not selected from among those who underwent a polysomnography may have affected the study results.…”
Section: Discussionmentioning
confidence: 94%
“…Teberik et al [ 33 ] conducted a prospective case–control study including 103 patients with OSA. The mean IOP values of patients with OSA were non-significantly lower than those of the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, a total of 19 studies with 316,178 participants were included in this review [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The diagnosis of OSA was based on the AHI measured using polysomnography or home sleep-apnea testing.…”
Section: Discussionmentioning
confidence: 99%